Evidência clínica do uso de métodos profiláticos orais relacionados a pneumonia associada à ventilação mecânica - Nascimento, Emmeline Bastos Ferreira do (2017)
Mechanical ventilation pneumonia (VAP) is defined as pneumonia that develops 48 hours after the beginning of invasive mechanical ventilation, and is considered up to 48 hours after extubation. Patients using the orotracheal tube (TOT) presented a deficit for self-care, showing a greater susceptibility to biofilm accumulation in the buccal cavity, favoring the incidence of nosocomial pneumonia in the Intensive Care Unit (ICU). Thus, this study aimed to carry out a systematic review on the main oral prophylactic methods used in the prevention of VAP. Search sources were PubMed, Scopus and Cochrane databases from May 23, 2017 through May 26 of this year. The selected studies evaluated the efficacy of oral antimicrobials in mechanically ventilated patients in controlled randomized controlled trials (RCTs) according to inclusion criteria. Papers presenting non-established themes, animal studies, patents and systematic reviews were excluded from the process. After analyzing the data, the articles were classified according to the level of evidence. The results showed that of the 503 abstracts found, of these, 15 articles included the review criteria. The selected studies indicated as prophylactic oral methods used in ECRC: chlorhexidine, Listerine, iodo-povidine and ceftazidime. It was observed in the 15 chosen articles that 8 presented unsatisfactory results for the reduction of VAP. In this perspective, the oral prophylactic methods applied in patients admitted to the ICU found in clinical trials were not favorable to the reduction of VAP indexes.